Peningkatan Kesadaran Hukum Masyarakat tentang Bahaya Narkotika di Desa Kawahmanuk, Kuningan - Yuhandra, Erga; Hidayat, Sarip; Akhmaddhian, Suwari; Anugrah, Dikha; Dialog, Bias Lintang; Yudistira, Dony; Sundari, Pipi (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2024)
Narcotics, Psychotropics and Addictive Substances other normal called Drugs is type drugs/substances needed in the world of medicine. However if used without strict restrictions and supervision can cause dependency as well as can endanger health even soul the user. Devotion to public with counseling law This aim For give knowledge and understanding about types drugs, consequences its abuse, the mode of distribution, and how method prevention. Implementation method devotion society This that is with method counseling law with stage hearing, implementation, evaluation report results and Discussion effort prevention and eradication to misuse and distribution dark drugs need done in a way comprehensive and multidimensional. try remove view that problem misuse and distribution dark drugs No only problem government course, but is a must problem handled by everyone.